Respuesta :

Answer:

x = - 9, x = 0, x = 7

Step-by-step explanation:

Given

[tex]\frac{1}{2}[/tex] x(x - 7)(x + 9) = 0 ← in standard form

Equate each factor to zero and solve for x

[tex]\frac{1}{2}[/tex] x = 0 ⇒ x = 0

x - 7 = 0 ⇒ x = 7

x + 9 = 0 ⇒ x = - 9

Answer:

-9, 0, 7

Step-by-step explanation:

Finding the roots of a polynomial equation is the same as solving the equation. So, simply figure out which values make the equation equal 0.

If multiplication is involved, then 0 is always an answer (or root). Because anything multiplied by 0 is always 0.

7 is also a root:

7 - 7 = 0

Same with -9:

-9 + 9 = 0

ACCESS MORE